Efisiensi Manajemen Pendidikan Islam melalui Penggunaan Aplikasi Teknologi Pendidikan - Suroso (An Nafi': Multidisciplinary Science, 2024)
The purpose of this study is to explore and identify ways to improve the efficiency of Islamic education management through the use of educational technology applications. Using library research methods, which rely on written sources such as books, scientific journals, and articles to collect and analyze data related to Islamic education management and the use of technology applications in education. Data are analyzed in depth to find patterns and information gaps, with a focus on verifying credible and relevant sources. This paper found that lack of access to integrated educational applications, minimal training of educators, and resistance to change are major obstacles to the efficiency of Islamic education management. Limited infrastructure, especially in remote schools, and high costs of implementing technology exacerbate the situation. Many schools still use manual methods due to low digital literacy among teachers and minimal technical support. Unstable internet connections also hinder the implementation of technologies such as IoT. To improve efficiency, intensive training, management support, and provision of adequate infrastructure are needed.